Review and extension of pressure drop models applied to Taylor flow regimes. (January 2015) - Mac Giolla Eain, Marc; Egan, Vanessa; Howard, James; Walsh, Patrick; Walsh, Edmond; Punch, Jeff
Highlights: Pressure drop in both liquid–liquid and liquid–gas Taylor flow regimes was measured. Liquid–gas correlations model the liquid–gas data well, all within +20%. A viscosity ratio was found, above which liquid–gas correlations can model liquid–liquid data. A modified Warnier model is proposed to model the liquid–liquid data below this viscosity ratio threshold. Abstract: This paper investigates the pressure drop induced by both liquid–liquid and liquid–gas segmented Taylor flow regimes. A comprehensive experimental programme was completed using four different liquid–liquid and three different liquid–gas combinations over dimensionless slug length, Reynolds and Capillary numbers that spanned several orders of magnitude. Comparisons between the liquid–liquid pressure drop data and the most referenced expressions in the literature highlighted their lack of robustness and demonstrated their inapplicability for use with most practical systems that incorporate liquid–liquid Taylor flow regimes. The experimental pressure drop values obtained for the liquid–gas flows agreed well with existing pressure drop correlations. Interpretation of the liquid–liquid data using liquid–gas models unearthed the existence of a threshold viscosity ratio. Above this threshold, experimental liquid–liquid data was found to agree well with existing liquid–gas models. Below this threshold, results showed that the dispersed slug velocity needed to be considered as the flows were subject to higher interfacial contributions and inertial effects. A modification is proposed to an existing liquid–gas pressure drop correlation. This proposed modification extends the applicability of the correlation to liquid–liquid flows, and furthermore extends the non-dimensional limits of the correlation.